Safer places the planning system and crime prevention. - Davies, Llewelyn (Thomas Telford, 2004)
Sustainable communities are communities which succeed now economically, socially and environmentally, and respect the needs of future generations. They are also well-designed places where people feel safe and secure; where crime and disorder, or the fear of crime, doesn't undermine quality of life or community cohesion. This is why the new Planning Policy Statement (PPS) 1, the overarching PPS setting out the Government's planning objectives, will highlight the need to plan for sustainable communities.